Prediction of Active Learning by Evaluating the Components of Competency and Teaching Quality in the Students of Mazandaran University of Medical Sciences - Kobra Aligolbandi; Pezhman Mohamadalizadeh; Fataneh Amue; Nasim Ghanhrani; Aliasgar Nadi ghra; Aref Hosseinian (Zanjan University of Medical Sciences and Health Services, 2018)
Background & Objective: Competency and teaching quality of professors play a key role in the quality of active learning in students. The present study aimed to predict the components of competency and teaching quality of professors regarding active learning in the students of Mazandaran University of Medical Sciences, Iran. Materials and Methods: In this study, 359 students were selected via stratified random sampling, and Cochran's formula was used to determine the sample size. Validity of three questionnaires was assessed using content validity and face validity, and the reliability was determined at the Cronbach's alpha of 0.853 for the questionnaire of professors' competency, 0.894 for the questionnaire of teaching quality, and 0.938 for the questionnaire of active learning in students. Data analysis was performed using parametric tests. Results: Variables of professors' competency, teaching quality, and active learning in students were estimated to be above average at the significance level of 0.001 in the affiliated schools. A significant association was observed between teaching quality and professors' competency at the significance of 0.001 and correlation-coefficient of 0.65. In addition, there was a significant association between teaching quality and active learning at the significance of 0.001 and correlation-coefficient of 0.61. Our findings indicated a linear correlation between the variables of competency and teaching quality compared to active learning (F=126.958; P=0.0001). Conclusion: According to the results, there seems to be a significant correlation between teaching quality and professors' competency, which could predict the level of active learning in students